Effect of lower-limb compression clothing on 400-m sprint performance - Faulkner, J. A.; Gleadon, D.; McLaren, J.; Jakeman, J. R. (The Journal of Strength and Conditioning Research, 2013)
This study investigated the effects of wearing a variety of lower-limb compression garments on 400-m sprint performance. Eleven 400-m male runners (23.7 ± 5.7 years, 1.78 ± 0.08 m, and 75.3 ± 10.0 kg) completed six, 400-m running tests on an outdoor, all-weather running track on separate occasions. The participants completed 2 runs with long-length lower-limb compression garments (LG; hip-to-ankle), a combination of short-length lower-limb compression garments (SG; hip-to-knee) with calf compression sleeves (ankle-to-knee), or without compression garments (CON; shorts), in a randomized, counterbalanced order. Overall lap time and 100-m split times, heart rate, and ratings of perceived exertion (RPEs) were measured during the 400-m run. Blood lactate concentration, visual analogue scales for perceived soreness, feeling and arousal, and scales for perceived comfort and tightness when wearing compression garments, were assessed before (preexercise, post-warm-up) and after 400-m performance (post, 4 minutes postexercise, after a warm-down). Statistical analysis revealed no differences between conditions in overall 400-m performance, 100-m split times, or blood lactate concentration (p > 0.05), although there was a trend for an increased rate of blood lactate clearance when wearing compression garments. A significantly lower RPE (p > 0.05) was however observed during LG (13.8 ± 0.9) and SG (13.4 ± 1.1) when compared with CON (14.0 ± 1.0). This study has demonstrated that lower-limb compression garments may lower the effort perception associated with 400-m performance, despite there being no differences in overall athletic performance.